2018
DOI: 10.1016/j.micinf.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Recent findings related to immune responses against leptospirosis and novel strategies to prevent infection

Abstract: What are the new approaches and emerging ideas to prevent leptospirosis, a neglected bacterial re-emerging zoonotic disease? How do Leptospira interrogans escape the host defenses? We aim here to review and discuss the most recent literature that provides some answers to these questions, in particular data related to a better understanding of adaptive and innate immunity towards leptospires, and design of vaccines. This is an opinion paper, not a comprehensive review. We will try to highlight the new strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 88 publications
3
29
0
Order By: Relevance
“…Thus, this work paves the way to the design of new prophylactic strategies against leptospirosis. Although a universal vaccine against leptospires is still a long-term goal [3], we envision the use TLR and/or NLR combined agonists, which are known to train immunity, as adjuvants for future leptospiral vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this work paves the way to the design of new prophylactic strategies against leptospirosis. Although a universal vaccine against leptospires is still a long-term goal [3], we envision the use TLR and/or NLR combined agonists, which are known to train immunity, as adjuvants for future leptospiral vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, vaccination is possible only in certain contexts, like in endemic areas when the circulating serovars are known. A few human vaccines based on inactivated whole bacteria are available, but they confer only serovar-specific and short-term protection [3]. In the absence of prophylactic drugs, preventive antibiotic therapy and wearing adapted clothes constitute the most effective prevention against this neglected disease.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine trials with the C‐terminal domains of LigA have shown protection that is more consistent than with other Lig protein segments (Adler, ). While these results suggest a possible link between domain stability and protection consistency, leptospirosis challenge experiments have many notable issues, including the animal model (Gomes‐Solecki, Santecchia, & Werts, ), the challenge strain (Fouts et al, ), the delivery method (Coutinho et al, ), and the use of adjuvants, that can each cause variability between vaccine trials (Vernel‐Pauillac & Werts, ). Comparing two recent LigB studies that used different adjuvants, the trial that incorporated the potent Alum adjuvant provided sterilizing immunity (Conrad et al, ), whereas the other trial used mycobacterial‐derived Freund adjuvant and did not provide complete protection (Evangelista et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, human cells largely failed to be stimulated by Leptospira lipid A, and rather have been shown to primarily utilize TLR2 activity against leptospiral LPS ( Nahori et al, 2005 ). In addition to human and mice, porcine and bovine cells also respond to Leptospira LPS through TLR2 ( Guo et al, 2015 , 2016 ; Vernel-Pauillac and Werts, 2018 ). In a study comparing the TLR2 profiles of mice (resistant) and hamsters (susceptible) against L. interrogans serovar Autumnalis, mice showed a quick induction of TLR2 while hamsters had a significantly delayed TLR2 response in the kidney, liver, and the lung ( Zhang et al, 2016 ).…”
Section: The Complicated Relationship Of Leptospira mentioning
confidence: 99%